2002
DOI: 10.1186/1471-2393-2-6
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune response to an allogenic foetus in normal fertile women and recurrent aborters

Abstract: BackgroundSeveral humoral immune factors are responsible for a successful pregnancy. There are a few studies, which demonstrate the role of antipaternal cytotoxic antibodies (APCA) and mixed lymphocyte reaction blocking factor (MLR-Bf) in the maintenance of pregnancy. However, these factors have not been studied in women with history of recurrent spontaneous abortion (RSA). We designed this study to review the role of APCA and MLR-Bf in normal pregnancy as well as in women with a history of RSA.MethodsOne hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…This apparent difference is in concordance with previous studies where circulating alloreactivity was reported in 20 -50% of women with successful pregnancies compared with less than 10% in women with abortions [4,5,13,14,21,22]. One explanation for the higher proportion of sensitized subjects among multipara could be the longer exposure time to the fetus in normal pregnancy, which may give more opportunities to induce a humoral immune response.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This apparent difference is in concordance with previous studies where circulating alloreactivity was reported in 20 -50% of women with successful pregnancies compared with less than 10% in women with abortions [4,5,13,14,21,22]. One explanation for the higher proportion of sensitized subjects among multipara could be the longer exposure time to the fetus in normal pregnancy, which may give more opportunities to induce a humoral immune response.…”
Section: Discussionsupporting
confidence: 92%
“…In most of the earlier studies, cell-based techniques for alloantibody detection, such as leukoagglutination [2,21], CDC [1,5,12,13,22], or flow-cytometric cross-matching [26,27] were used to detect alloantibodies. A weakness of cell-based assays is their failure to distinguish between HLA-specific alloantibodies and antibodies directed to non-HLA antigens expressed on the surface of test lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the fetus can be considered as a semiallograft, because half its MHC genes are of paternal origin, it may be recognized as non-self by the mother and consequently rejected in case of inadequate placental counteraction of maternal immunity [21].…”
Section: Discussionmentioning
confidence: 99%
“…T he induction of antibodies that target paternal leukocyte antigens resulting from pregnancies is a well-described immunological phenomenon in human gestation (1)(2)(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%